THE CONSTRUCTION OF BALINESE WOMEN'S IDENTITY IN THE NOVEL SUKRENI GADIS BALI - Sutrisno, Nanang; Isnu Maharani, Sang Ayu; Sukarma, I Wayan (E-Journal of Cultural Studies; Vol 16 No 3 (2023): Volume 16 Number 3 August 2023, 2023)
Novel is not just a literary work, but also serves to dismantle various cultural practices in society. The novel Sukreni Gadis Bali is one of many novels that represents feminist literary criticism. It can take part as participatory and emancipatory roles for gender equality in Bali. In the sociolinguistic approach, literary works can take on an ideological role for social transformation by criticizing deviations from cultural practices that result in injustice to certain social groups. Having this background, this research intends to explore Balinese women’s identity construction in the novel Sukreni Gadis Bali. This research applies a qualitative method with a critical discourse analysis approach and note taking technique. The main literature reviewed is the novel entitled Sukreni Gadis Bali by Panji Tisna which is analysed using a critical interpretation. This research found that the identity of Balinese women involves the role of structure in the form of a naming system, culture in the form of patriarchal relations, and actors in the form of identity awareness. It also found that the construction of identity can lead to identity fracture in the social world which resulting in various physical impacts. In addition, the construction of Balinese women’s identities is under the control of patriarchal ideology. The ideology is naturalized in the patrilineal kinship, religious, and customary system. Sukreni is a symbol of a Balinese woman whose identity has been degraded by culture, so she has to accept various forms of violence and injustice throughout her life's journey. Keywords : Balinese women, construction, identity, novel